Conversion of placental hemogenic endothelial cells to hematopoietic stem and progenitor cells - Guixian Liang; Shicheng Liu; Chunyu Zhou; Mengyao Liu; Yifan Zhang; Dongyuan Ma; Lu Wang; Jing-Dong J. Han; Feng Liu (Cell Discovery)
Abstract Hematopoietic stem and progenitor cells (HSPCs) are critical for the treatment of blood diseases in clinic. However, the limited source of HSPCs severely hinders their clinical application. In the embryo, hematopoietic stem cells (HSCs) arise from hemogenic endothelial (HE) cells lining the major arteries in vivo. In this work, by engineering vascular niche endothelial cells (VN-ECs), we generated functional HSPCs in vitro from ECs at various sites, including the aorta-gonad-mesonephros (AGM) region and the placenta. Firstly, we converted mouse embryonic HE cells from the AGM region (aHE) into induced HSPCs (iHSPCs), which have the abilities for multilineage differentiation and self-renewal. Mechanistically, we found that VN-ECs can promote the generation of iHSPCs via secretion of CX3CL1 and IL1A. Next, through VN-EC co-culture, we showed that placental HE (pHE) cells, a type of extra-embryonic HE cells, were successfully converted into iHSPCs (pHE-iHSPCs), which have multilineage differentiation capacity, but exhibit limited self-renewal ability. Furthermore, comparative transcriptome analysis of aHE-iHSPCs and pHE-iHSPCs showed that aHE-iHSPCs highly expressed HSC-specific and self-renewal-related genes. Moreover, experimental validation showed that retinoic acid (RA) treatment promoted the transformation of pHE cells into iHSPCs that have self-renewal ability. Collectively, our results suggested that pHE cells possess the potential to transform into self-renewing iHSPCs through RA treatment, which will facilitate the clinical application of placental endothelial cells in hematopoietic cell generation.